Three galleries of the Anthropocene. (December 2014) - Robin, Libby; Avango, Dag; Keogh, Luke; Möllers, Nina; Scherer, Bernd; Trischler, Helmuth
This paper considers three 'galleries' that explore the Anthropocene in cultural ways, and the implications of the Anthropocene idea for cultural institutions and heritage. The first gallery is the 2014–2016 exhibition Welcome to the Anthropocene: The Earth in Our Hands, [ Willkommen im Anthropozän: Unsere Verantwortung für die Zukunft der Erde ] at the Deutsches Museum in Munich. The second 'gallery' of Anthropocene Posters sponsored by the Art Museum, Haus der Kulturen der Welt (HKW), placed the Anthropocene in a 'museum without walls' in the streets of Berlin in 2013. The third 'gallery of the Anthropocene', was not a museum, but rather a landscape gallery (or 'spectacle') of in situ industrial heritage in Svalbard. Pyramiden, a town established to mine coal well north of the Arctic Circle in the early 20th century, has been recently transformed as an attraction for climate change science and heritage tourism. Here the hybridized local landscape creates a snapshot of the Anthropocene, bringing together industrial coal-mining heritage buildings, polar tourism and science forged in the geopolitics of the changing Arctic environment.